Perilaku Masyarakat Gampong Surien Kota Banda Aceh terhadap Pengelolalaan Sampah Rumah Tangga - Zubir Zubir (Universitas Serambi Mekkah, 2018)
The environment is an integral part of human life so environmental problems such as household waste problems are related to everyday human life, both in individual life and environment.The author encounters many garbage housewives are thrown out of place so scattered and cause unpleasant odor and fly flies. Purpose of research: to know the behavior of society to waste housewife management at Gampong Surien Kota Banda Aceh. This research method is Survey research that is descriptive Analytical with Cross Sectional design. The population is housewives in Gampong Surien Kota Banda Aceh totaling 451people. The sampling technique used in this research is using Systimatika random sampling with the number of samples as many as 82 people with independent variables are garbage collection, garbage transportation, waste management and disposal while the dependent variable is the behavior in household waste management. Data were collected using questionnaire and data analysis technique using statistical test (chi-square) with significance level 95% (p